Digital Device Usage and Cyber-aggression: An Analysis of Online Aggressive Behavior Patterns on Digital Platforms in Indonesia - Nurfitriany Fakhri (PT ARRUS Intelektual Indonesia, 2025)
This study examined the relationship between digital device usage and cyber-aggression among Indonesian young adults, focusing on platform-specific patterns and gender differences. Using a descriptive-correlational design, 561 participants aged 18-35 completed the Cyber-aggression Types Questionnaire and Digital Device Usage Questionnaire, measuring seven aggression types and usage across eleven digital platforms. Results revealed flaming (26.9%) and trolling (20.0%) as the most prevalent cyber-aggression forms. A significant positive correlation emerged between overall digital device usage and cyber-aggression. Platform-specific analysis showed particularly strong correlations with video gaming, online gambling, dating apps, cybersex platforms, and anonymous sharing websites, whereas mainstream platforms like social networking sites and instant messaging showed weak or non-significant correlations. Gender differences were substantial: males reported significantly higher frequencies across all cyber-aggression types and more intensive use of gaming, gambling, and anonymous platforms. Females showed higher engagement with social networking and media sharing platforms. These findings highlight how cyber-aggression manifests differently across digital environments and is influenced by both platform characteristics and gender-based usage patterns. The study underscores the importance of moving beyond generalized digital usage measures to consider specific platform affordances and gendered behaviors when addressing online aggression. Implications include developing targeted digital literacy programs, creating platform designs that balance privacy with accountability, and implementing gender-sensitive intervention strategies to effectively reduce cyber-aggression in Indonesia's evolving digital landscape.